Pengaruh Pengetahuan Kewirausahaan, Kompetensi Sosial dan Lingkungan Bisnis Terhadap Pertumbuhan Usaha Café di Kota Banda Aceh - Nur Syifa (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2024)
The purpose of this research was to determine the partial and simultaneous influence of entrepreneurial knowledge, social competence, and the environment on the growth of cafe businesses in Banda Aceh. This study involved 48 cafe entrepreneurs in Banda Aceh. The research object related to entrepreneurial knowledge, social competence, and the environment's influence on cafe business growth in Banda Aceh. The data analysis method used was multiple linear regression analysis with SPSS. The results showed that entrepreneurial knowledge, social competence, and the cafe business environment in Banda Aceh influenced cafe business growth in Banda Aceh. Business owners must be willing to take risks, be able to analyze every opportunity, and be able to provide solutions to every problem. Attitudes and skills, both social and communication, are added values ​​for business owners to achieve the desired cafe growth.